Dynamic response of a functionally graded cylindrical shell subjected to swirling annular flow including the fluid viscous effects. (December 2017) - Ning, Wen-Bo; Zhong, Mingjun; Hu, Guangzhong; Luo, Yangjun
Highlights: The fluid rotational speed lowers the critical axial flow speed. The new physical coefficient Vr is defined. The coupling effect of the fluid rotation and viscosity on the dynamic behavior of shells. Abstract: Considering the fluid viscosity, the dynamic behavior of a functionally graded materials (FGMs) cylindrical shell conveying a swirling annular fluid in the annulus between the inner shell and the outer shell are investigated, where material properties are graded across the thickness of the S-FGM thin shell with metal-ceramic-metal layers according to a Sigmoid power law. The shell-vibration-induced inviscid fluid-dynamic forces are described in the frame of the potential flow theory; the steady viscous forces are established based on the time-averaged Navier-Stokes and continuity equations. The shell is modeled by Flügge's shell theory. The zero-level contour method, the Galerkin's method and the traveling-wave type solutions are used for dynamic analysis of the S-FGM shell. The results show effects of the fluid rotation, viscosity and material properties on the dynamic behavior of the S-FGM shell. The coupling influences of the fluid rotation and viscosity on the stability of the shell are evaluated. The critical annular flow velocity, at which the form of the stability loss begins to change, is found. Graphical abstract: The graphical abstract gives the coupling effect of the fluid viscosity and rotation on dynamic responses of the stainless steel and S-FGM shells. The steady viscous force induced by the fluid rotation has a strong destabilizing effect on the high viscosity fluid and weak-rigidity shell.